2016
DOI: 10.1136/bcr-2016-216758
|View full text |Cite
|
Sign up to set email alerts
|

Unexplained lymphadenopathies: autoimmune lymphoproliferative syndrome in an adult patient

Abstract: Autoimmune lymphoproliferative syndrome (ALPS) is characterised by massive enlargement of the lymphoid organs, autoimmune cytopenias and a predisposition to develop lymphoid malignancies. The basic defect is a disturbance of the lymphocyte apoptosis, and a high number of circulating TCRab CD3+CD4−CD8− T-cells (double-negative T cells (DNT cells)). We describe a case of a 41-year-old man with fever, hepatosplenomegaly, multiple lymphadenopathy, autoimmune haemolytic anaemia and severe thrombocytopenia. Peripher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
1
0
1
Order By: Relevance
“…genes such as FAS, FASL, CASP8 and CASP10, evaluation of STAT3, LRBA and CARD11 genes can be considered. The most common presentation was splenomegaly in 86.2% and hematologic disease in 83.7% of cases followed by autoimmunity in 83.6% of cases, this is the same as what had been observed in the previous studies (16,32,33). Shaili Shah Et.al reported that the earliest and the most common clinical manifestation of ALPS is chronic lymphadenopathy and/or splenomegaly.…”
Section: Parameters Alps-like (N=61)supporting
confidence: 84%
See 1 more Smart Citation
“…genes such as FAS, FASL, CASP8 and CASP10, evaluation of STAT3, LRBA and CARD11 genes can be considered. The most common presentation was splenomegaly in 86.2% and hematologic disease in 83.7% of cases followed by autoimmunity in 83.6% of cases, this is the same as what had been observed in the previous studies (16,32,33). Shaili Shah Et.al reported that the earliest and the most common clinical manifestation of ALPS is chronic lymphadenopathy and/or splenomegaly.…”
Section: Parameters Alps-like (N=61)supporting
confidence: 84%
“…Increased proportion of DNT cells is a required criterion in ALPS diagnosis whereas in our study only in half of patients (56.7%) elevated DNT cells was reported. In our study, elevated DNT cells didn't reported in patients with RASGRP1, KRAS, and ADA2 mutation (31,32).…”
Section: Parameters Alps-like (N=61)contrasting
confidence: 52%